The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00267-018-1033-6
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Find a Suitable Biomass for Biochar-Based Polypropylene Biocomposites

Abstract: Four biomass wastes (rice husk, coffee husk, coarse wool, and landfill wood) were added with biochar and polypropylene (PP) to manufacture biocomposites. Individual biomasses were tested for their combustion behavior using cone calorimeter. Biocomposites were analyzed for their fire/thermal, mechanical, and morphological properties. Wood had the most desirable comprehensive effect on both the mechanical and fire properties of composites. In particular, wood and biochar composite exhibited the highest values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…In the field of industry, thermoplastic-based composites are largely used with an annual production of up to 29.5% of the overall production [21]. Several studies have been reported about the production of biochar containing polyethylene [22][23][24] or polypropylene [25][26][27][28] that enhanced the mechanical and thermal properties of the host polymeric matrix. Nonetheless, few research efforts have been devoted to investigate the effect of biochar produced at high temperatures towards the enhancement of polymer conductivity [29].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of industry, thermoplastic-based composites are largely used with an annual production of up to 29.5% of the overall production [21]. Several studies have been reported about the production of biochar containing polyethylene [22][23][24] or polypropylene [25][26][27][28] that enhanced the mechanical and thermal properties of the host polymeric matrix. Nonetheless, few research efforts have been devoted to investigate the effect of biochar produced at high temperatures towards the enhancement of polymer conductivity [29].…”
Section: Introductionmentioning
confidence: 99%
“…Coffee wastes have been also used as feedstock for pyrolytic conversion producing hydrogen-rich gas [8] and fuel-quality biochar [9]. Biochar has been used not only as solid fuel but also as high performance material [10,11], as a flame retardant additive [12,13], for electrochemical [14] and energy storage applications [15] and for production of composites [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, limited recyclability and non-biodegradability of carbon fibre have become a growing concern when disposing of waste end of life products. Studies carried out by Das et al [32] highlighted that wood and biochar biocomposites exhibited highest mechanical properties (tensile and flexural) and improved fire resistant behaviour when compared to other waste biomasses. Additionally, hybridisation was used to improve mechanical properties as well as limiting oxygen index of waste-based biochar/wood hybrid composites [33].…”
Section: Introductionmentioning
confidence: 99%